2019
DOI: 10.22146/jfs.35551
|View full text |Cite
|
Sign up to set email alerts
|

The 16S and COI Mitochondrial DNA Nucleotide Composition of Stripped Snakehead (Channa striata Bloch,1793) from Lake Sentani, Jayapura, Papua

Abstract: Stripped snakehead (Channa striata Bloch,1793) has potency to be developed in Indonesia due to high nutritional value including omega 3 which is useful for children growth. However, study on composition of mitochondrial DNA nucleotide as a part of study on genetic characterization of stripped snakehead fish in Indonesia is poorlyunderstood. Genetic characterization of stripped snakehead is important to obtain data information that can be applied for breeding and conservation program. Therefore, the objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
5
2
0
Order By: Relevance
“…We found that P. kalolo samples from Bogowonto were in the same clade as samples from Baros Beach (MZ614852, MZ614847), Cilacap (KU692753), but in a different clade compared to samples from Baros Beach (MZ614840-42, MZ614844-46, MZ614848-49, MZ614850-51, MZ614853-54), Tulungagung (KU692750, KU692751, KU692751, KU692755, KU692747, KU692748), and other samples from Cilacap (KU692754). These results are consistent with previous research by Arisuryanti et al (2018) and Aji and Arisuryanti (2021). Additionally, we also observed that P. argentilineatus from Baros Beach (MZ606684-86) were in the same clade as samples from Pandeglang (KU692744-46) and samples from Bogowonto (MT4359598-600), separated from the clade with P. argentilineatus from Baros Beach (MZ606687) and a sample from Tukad Bilukpoh, Jembrana Bali (KU692743) (Dahruddin et al 2017;Aji & Arisuryanti 2021).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…We found that P. kalolo samples from Bogowonto were in the same clade as samples from Baros Beach (MZ614852, MZ614847), Cilacap (KU692753), but in a different clade compared to samples from Baros Beach (MZ614840-42, MZ614844-46, MZ614848-49, MZ614850-51, MZ614853-54), Tulungagung (KU692750, KU692751, KU692751, KU692755, KU692747, KU692748), and other samples from Cilacap (KU692754). These results are consistent with previous research by Arisuryanti et al (2018) and Aji and Arisuryanti (2021). Additionally, we also observed that P. argentilineatus from Baros Beach (MZ606684-86) were in the same clade as samples from Pandeglang (KU692744-46) and samples from Bogowonto (MT4359598-600), separated from the clade with P. argentilineatus from Baros Beach (MZ606687) and a sample from Tukad Bilukpoh, Jembrana Bali (KU692743) (Dahruddin et al 2017;Aji & Arisuryanti 2021).…”
Section: Discussionsupporting
confidence: 94%
“…This result is consistent with the study by Ward et al (2005) which discovered a total GC content COI ranging from 42.2-47.1%. Additionally, we found a T>C>A>G nucleotide composition pattern of the COI gene that was comparable to studies in other fish families (Bingpeng et al 2018;Kombong & Arisuryanti 2018;Wu et al 2018;Linh et al 2018;Aji & Arisuryanti 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study showed that the Channa striata COI nucleotide composition pattern is T>C>A>G, a pattern typical within the Teleostei and the Pisces superclass in general (Chen et al 2016;Osho et al 2021), but contrast with base composition of the C. striata from Thailand (Boonkusol and Tongbai 2016), and different from the nucleotide composition of some fishes such as the Asian seabass (Lates calcarifer) (Irmawati et al 2020). The same COI nucleotide pattern was also reported by Kombong and Arisuryanti (2018) in C. striata in Lake Sentani Jayapura Papua and in African snakehead Parachanna obscura in Nigeria's freshwater (Osho et al 2021). The guanine and cytosine (GC) content of C. striata in this study was less than 50%, ranging from 45.60% to 46.21%.…”
Section: Discussionsupporting
confidence: 82%